The Cost of Urban Waste Management: An Empirical Analysis of Recycling Patterns in Italy - Cialani, Catia; Mortazavi, Reza (Frontiers in Sustainable Cities, 2020)
Italy is facing high pressure to meet objectives to recycle waste and national waste management targets set by the European Union Waste Framework Directive (2008/98/EC; EC European Commission, 2008). However, waste collection and recycling waste costs pose major problems (addressed here) at municipal level for the Italian waste management system. The empirical literature on waste management has paid much more attention to demand-side aspects (reduction and discouragement of land disposal and promotion of recycling and recovery) than to supply-side issues such as analysis of waste management costs. This paper addresses the gap in this research field by estimating the cost function of providing waste collection and recycling services for Italian municipalities during the years 2011–2017. Specifically, we estimate cost elasticity and marginal costs to determine if there are economies of scale for recycling urban waste. Our findings suggest that increasing recycling rates would not substantially increase total costs for most of the municipalities, so recycling should be encouraged, especially for municipalities with low recycling rates. In particular, we observe that cost elasticity is higher in northern municipalities than in central and southern Italian municipalities. Our cost function exhibits economies of scale until a certain amount of recycled waste. The results provide insights into the cost structure of recycling that may lead to more efficient waste management.